2010
DOI: 10.1016/j.trac.2010.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Sensors for measuring biodegradable and total organic matter in water

Abstract: This critical review spans the past two decades and outlines sensors developed for measuring total (TOM) and biodegradable organic matter (BOM) in water. We report the state of the art of the most significant technologies. Although the focus is on in situ devices, we also mention on-line techniques able to lead to sensors sensu stricto and discuss them as possible emerging technologies. We divide the review into sections: (1) TOM; and (2) BOM. We first briefly outline each technique then analyze the published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 89 publications
(64 reference statements)
0
18
0
Order By: Relevance
“…68 Previous studies have noted that Geobacter species have pili on their cell membrane, which are able to transfer electrons to the anode surface easily. 69 The pili or flagella provide to perform direct electron transfer and therewith high-power density. It was reported that the Comamonas sp.…”
Section: Community Analysismentioning
confidence: 99%
“…68 Previous studies have noted that Geobacter species have pili on their cell membrane, which are able to transfer electrons to the anode surface easily. 69 The pili or flagella provide to perform direct electron transfer and therewith high-power density. It was reported that the Comamonas sp.…”
Section: Community Analysismentioning
confidence: 99%
“…In contrast, a number of attentions have been paid to the development of organics sensors based on another green method of photocatalytic degradation. [4][5][6] The only reason we deduce is the lack of a sensitive and robust probe of the Fenton reaction under highly oxidizing conditions. A catalyst, typically transition metal ions with variable valences such as iron(II), is usually required in the Fenton oxidation to promote the process.…”
Section: Plasmonic Swings During Fenton Reaction: Catalytic Sensing Omentioning
confidence: 91%
“…As the Fenton reaction is strongly influenced by the medium pH, we also investigated the reaction under different pH (1)(2)(3)(4)(5)(6)(7). It can be seen from Fig.…”
Section: Plasmonic Swings During Fenton Reaction: Catalytic Sensing Omentioning
confidence: 99%
“…In addition, MCF has become the mostly studied method. The main issues in the development of new detection methods involve time-consuming preparation procedures [4,12,26], longer incubation or activation or measurement times [4,12,26,29,30], rigorous maintenance [26,31], online applications [26,32], and complex analysis systems [26,33]. Although MFCs can generate stable current under constant condition, the pollution of toxic substances in MFCs usually reduces the current by affecting microorganisms [34,35].…”
Section: Introductionmentioning
confidence: 99%